ASSESSMENT OF RESPIRATION‐INDUCED DISPLACEMENT OF CANINE ABDOMINAL ORGANS IN DORSAL AND VENTRAL RECUMBENCY USING MULTISLICE COMPUTED TOMOGRAPHY. Issue 2 (18th August 2014) - Oliveira, Cintia R.; Henzler, Margaret A.; Johnson, Rebecca A.; Drees, Randi
<x xml:space="preserve">Abstract</x> Respiratory‐induced organ displacement during image acquisition can produce motion artifacts and variation in spatial localization of an organ in diagnostic computed tomography (CT) examinations. The purpose of this prospective study was to quantify respiratory‐induced abdominal organ displacement in dorsal and ventral recumbency using five normal dogs. All dogs underwent CT examinations using 64 multidetector row CT (64‐MDCT). A "3‐dimensional (3D) apneic CT exam" of the abdomen was acquired followed by a "4‐dimensional (4D) ventilated CT exam." The liver, pancreas, both kidneys, both medial iliac lymph nodes, and urinary bladder were delineated on the 3D‐apneic examination and the organ outlines were compared to the maximum alteration in organ position in the 4D‐ventilated examination. Displacement was measured in dorsal‐to‐ventral (DV), right‐to‐left (RL), and cranial‐to‐caudal (CC) directions. Respiratory‐induced displacement of canine abdominal organs was not predictable and showed large variability in the three directions evaluated. For most canine abdominal organs, dorsal recumbency provided overall the least amount of displacement among all directions evaluated except for liver and urinary bladder. For liver, a large variability was found for all directions and a statistically significant difference was found only in the RL direction with ventral recumbency exhibiting less displacement (P = 0.0099). For the urinary bladder, ventral recumbency also provided less displacement but this was statistically significant only in the RL direction (P < 0.0001). Findings from this study indicated that dorsal recumbency may be preferred for minimizing respiratory motion artifacts in whole abdomen studies, but ventral recumbency may be preferred for liver and urinary bladder studies when respiration cannot be controlled.